Teaching Cultural Competence and Social Justice in a Mental Health Counseling Graduate Course: Reflection and Review of the Literature - Mary Beth Medvide (Journal for Social Action in Counseling and Psychology)
Cultural competence and commitment to social justice are foundational to counselors’ professional identity. There is significant attention in scholarly literature and ethical codes on what this means for the education, training, and practice. This has led counseling and counselor education programs to actively incorporate issues of cultural diversity and social justice into coursework and fieldwork requirements. Research trends indicate graduate students in counseling and counselor education benefit personally and professionally from the knowledge, skills, and awareness they develop in and outside of the classroom. Coursework on multiculturalism and social justice is a standard part of these programs, but knowledge on best practices for students’ personal and professional growth is still accumulating to reflect dynamic social and political changes within the United States and abroad. This manuscript describes a required counseling course for mental health counseling students implemented in the spring of 2020. This course integrated topics related to cultural diversity and social justice and introduced conceptual frameworks for counseling and advocacy. The description of this course includes sample readings, in-class activities, and graded assignments that fulfill the learning objectives. Comparisons to research trends and existing recommendations are made, and future directions for course design are highlighted.